CONSTRUCTION OF PRECISE GEOMETRIC ELEMENTS ON THE PLANE ON THE EARTH MODEL - Meyliyev To‘lqin Meyli o‘g‘li; Ibragimov Mirjahon Ilhom o‘g‘li; Narziboboyev Anvar Abduxoliq o‘g‘li (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, automatic calculation of accurate geometric elements and bar-code level on the plane on the ground model and modern technologies, i.e. Dini 11, Dini 21, Carl Zeiss, Dini 12, Dini12T, Dini22 Trimble, DNA03, Measures to introduce DNA10 Leica and other digital techniques were studied.